Analysis of the President's Budget for 2013 - Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 2013)
This study presents an evaluation of the National Expenditure Program for 2013. First, this paper projects that the fiscal targets set out in the Budget of Expenditures and Sources of Financing (BESF) for 2013 are likely to be met. Specifically, fiscal deficit is projected to be PHP 9.6 billion lower than the BESF at PHP 231 billion, while government revenue is estimated to be equal to PHP 1.8 trillion in 2013 which is also higher than the BESF projection. This is despite the expectation that the BOC collections and nontax revenues will be just equal to the 2011 and 2012 levels. Additional revenues is thus sourced from the BIR collections, which is estimated to reach PHP 1.26 trillion in 2013, exceeding the President's Budget's estimate of PHP 1.24 trillion. Second, although a more balanced distribution of the budget between the social services and economic services sectors is emphasized in the 2013 National Expenditure Program, the services sector still accounts for more than half of the increase in expenditure program in 2013. Finally, the improving debt profile of the country will continue in 2013. National government borrowing will continue to be biased in favor of domestic borrowings.
Keywords: 330; fiscal deficit; tax effort; fiscal sustainability; expenditure program; Philippines; budget share; revenue program; financing program